Computational Thinking Ability in Learning in Terms of Learning Style and Gender - Netti Kariani Mendrofa; Edi Syahputra; Elmanani Simamora (Universitas Serambi Mekkah, 2024)
This study aims to analyze students' computational thinking ability based on learning style and gender in basic mathematics courses. The research sample was students of the mathematics education study program, FKIP, Nias University in the first semester of the 2023/2024 academic year. This research is a quantitative descriptive research. This type of data analysis technique uses quantitative data analysis. The instruments used are learning style questionnaire and computational thinking ability test. The results showed that learning style and gender have a significant influence on the average score of students' computational ability.